PERBANDINGAN SISTEM HUKUM TENTANG REGULASI KEJAHATAN TANPA KORBAN DI KAWASAN ASIA - Handoko, Duwi; Sukri, Beni (Ensiklopedia Sosial Review, 2019)
Victimless crime is an important thing to know, both in terms of aspects related to crime patterns and imposition of sanctions against violator. The reason is that it is not appropriate to punish someone who does not harm others.In a discussion that the author does, it is not appropriate if someone is punished for having the potential to become a "criminal". An illustration of this can be read in this research. This research was conducted to reveal the comparison of the legal system (similarities and differences between Civil Law, Common Law, and Islamic Law) related to crime without victims in the Asian region. To achieve these objectives, the research method applied is normative legal research with the nature of descriptive research. The equation of the Civil Law, Common Law, and Islamic Law systems related to the regulation of crime without victims in the Asian region is only an aspect of prohibiting illegal drug users. Whereas the differences are: In the context of gambling players: Indonesia, which implements Civil Law and Saudi Arabia that apply Islamic Law, expressly prohibits every citizen to play gambling, both in the real world and in cyberspace. Whereas in Malaysia, which applies a dual legal system (Islamic Law and Common Law), gambling is a limited legal act. What is that? And how is the comparison in the context of prostitution and narcotics users? The answer can be known from the results of this research.